Reconciling insurance with market discipline: A blueprint for a European fiscal union - Mathias Dolls; Clemens Fuest; Friedrich Heinemann; Andreas Peichl (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2015)
This contribution develops a blueprint for a European fiscal union. The proposal addresses the shortcomings of most other reform designs which do not offer a solution for insolvent or noncooperative euro countries. We suggest a design which combines fiscal insurance with an orderly procedure to restructure the debt of an insolvent euro member. We show that fiscal insurance and a sovereign insolvency procedure are no contradiction but, on the contrary, mutually enforcing: An effective fiscal insurance helps to limit the stability risks involved in the implementation of an insolvency regime for sovereigns. And vice versa, a well-defined insolvency procedure reduces the danger that a fiscal capacity motivated as an insurance against transitory asymmetric shocks degenerates into a permanent transfer system. Moreover, we show that both elements are a helpful complement for the functioning of the European banking union and the new European fiscal governance.
urn:nbn:de:bsz:180-madoc-394892
Keywords: H87; H12; 330; sovereign insolvency procedure; European unemployment insurance; euro area debt crisis